A New Approach to Internal Investigations as an Essential Component of Prevention Models in Peru - López Romani, Javier Eduardo (Revista de Derecho, 2025)
This paper examines internal investigations as an essential component of prevention models established under Law 30424 in Peru. Since the implementation of this regulation in 2017, supplemented by its 2019 decree, legal entities are required to adopt compliance programs or prevention models, known as Criminal Compliance, to mitigate the risks of criminal offenses. A key element of these models is the whistleblowing procedure, which includes internal investigations designed to identify crime indicators and ensure the validity of results.The study underscores the need to distinguish internal investigations from criminal investigations. The former are private, voluntary, and focused on organizational learning, while the latter are public, mandatory, and conducted by the Public Prosecutor’s Office with punitive and legal liability objectives. A paradigm shift is proposed to view internal investigations as tools for continuous improvement aimed at preventing misconduct, strengthening compliance culture, and ensuring the protection of fundamental rights of those involved.Finally, the paper highlights the complementary role of internal investigations in criminal processes and their capacity to foster internal trust by alleviating fears of disproportionate retaliation. This contributes to the strengthening of corporate integrity and organizational transparency.
Keywords: compliance; crime prevention models; internal investigations; criminal investigations